TRATEGI GURU DALAM MEMBENTUK KARAKTER DISIPLIN SISWA KELAS V DI SDN SERUT BARU GEDANGSARI - Aprilia Devi Nur Khasanah; Ridia Olivia Sholikhah; Ida Megawati (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2022)
There are still disciplinary violations that occur at the elementary school (SD) level. As was the case in class V at SDN Serut Baru Gedangsari, there were still some students who did not practice discipline, both in terms of time, attitude, and enforcing rules. From observations, it was found that students did not come on time, did not use the proper attributes and violated existing regulations. Therefore, teachers need to have a strategy to overcome this. In order to find out the teacher's strategy in shaping the disciplinary character of fifth grade students at SDN Serut Baru Gedangsari, we conducted a qualitative research to describe the teacher's strategy in shaping the disciplinary character of students. This research was conducted at SDN Serut Baru with the research subject being a class V teacher using the interview method.